Blunt Microdissection for Endovascular Treatment of Infrainguinal Chronic Total Occlusions. (February 2014) - Banerjee, Subhash; Hadidi, Omar; Mohammad, Atif; Alsamarah, Ali; Thomas, Rahul; Sarode, Karan; Garg, Puja; Baig, Mirza S.; Brilakis, Emmanouil S.
Purpose: To present a systematic safety evaluation of the CrossBoss blunt microdissection catheter for crossing peripheral chronic total occlusions (CTOs). Methods: Between July 2010 and July 2011, 15 patients (all men; mean age 60.7±9.1 years) underwent endovascular treatment of 17 infrainguinal CTOs that were resistant to guidewire passage, so the blunt microdissection catheter was employed to recanalize the artery. Fourteen lesions were de novo and 3 were in-stent restenoses. Sixteen lesions were in the superficial femoral artery; 8 of 17 CTOs were TASC II type D. Extensive calcification was present in 12 lesions. Mean lesion length was 182.9±66.2 mm (range 57–296). Results: Procedural success was 100% and successful crossing without the use of a re-entry device (technical success) was achieved in 15 cases. Twelve lesions were stented. Average fluoroscopy time was 36.5±21.2 minutes (143.8±76.9 Gy*cm 2 radiaton dose area product), during which a mean 172.1±62.2 mL of iodinated contrast were used. Two patients had access site hematomas that were treated conservatively, and there was no perforation, distal embolization, amputation, or need for urgent revascularization. During the mean follow-up of 11.4±0.1 months, 1 patient died, and none required an amputation or surgical revascularization. There was a significant improvement in ankle-brachial index (0.6±0.1 to 0.8±0.2, p=0.001) and symptoms as assessed by Rutherford class at 1 year. Four of 17 limbs required secondary revascularization procedures within 1 year. Conclusion: The CrossBoss blunt microdissection catheter facilitated successful crossing of CTOs in patients with infrainguinal lesions following unsuccessful guidewire crossing, with an acceptably low rate of periprocedural complications and significant improvement in symptoms.